PENGARUH VARIASI RASIO Si/Al STRUKTUR ZEOLIT A DAN VARIASI KATION (Li+, Na+, K+) TERHADAP PERUBAHAN UKURAN WINDOW ZEOLIT A MENGGUNAKAN METODE MEKANIKA MOLEKULER - Maria Amelia Kristianingrum; Rahmat Gunawan; Rudi Kartika (JURNAL KIMIA MULAWARMAN, 2016)
The structure modeling of zeolite A using calculation of molecular mechanics methods with variation of Si/Al ratio ( 1; 1,18; 1,4; 1,66 and 2) and variation of cations (Li+, Na+, K+) has been investigated. The result shows that the structure of zeolit A with the ratio of Si/Al = 2, has the most stable structure with a minimum energy 1757,1420 kcal/mol. The most stable zeolite A structure impregnated with cations are determined from the lowest energy which is 1686,8383 kcal/mol for the structure with K+ cation. In addition result shows that the structure with Li+ cation has the largest window diameter, thus affecting the window size of the zeolite A structure of which potentially has the best adsorbent capacity.